A novel prognostic biomarker DUSP6 promote the malignant progression of bladder cancer through mTOR mediated mitophagy - Huang, Jianbiao; Zhou, Chongwei; Yu, Zhaojun; Song, Zhen; Deng, Huanhuan; Chao, Haichao; Zeng, Tao (Frontiers in Oncology, 2025)
Bladder cancer (BC) is one of the most prevalent urinary malignant tumors that is intricately regulated by molecular pathways. Multiple studies have demonstrated a clear association between DUSP6 and malignant tumor progression; however, its role and underlying mechanisms in BC remain unclear. Here, we found that DUSP6 exhibits significantly elevated expression in BC tissues compared with normal tissues and is strongly associated with poor overall survival. Transcriptomic analysis revealed a robust correlation between DUSP6 expression and mitophagy, a selective form of autophagy crucial for maintaining mitochondrial integrity. In vitro and in vivo experiments demonstrated that knockdown of DUSP6 reduces tumor invasion, migration, and proliferation ability while enhancing mitophagy in BC cells. Notably, the anti-malignant effects of DUSP6 knockdown were partially reversed by the mitophagy inhibitor cyclosporin A. Mechanistically, DUSP6 modulates mitophagy by increasing the phosphorylation status of mTOR, a central autophagy regulator, and DUSP6 knockdown-induced mitophagy was partially restored after treatment with mTOR activator MHY1485. Our findings indicate that high DUSP6 expression promotes BC progression by inhibiting mTOR-mediated mitophagy, leading to a poor prognosis for BC patients. These insights suggest DUSP6 as a potential therapeutic target in the treatment of BC.